Impact of domestic debt on economic growth in Sierra Leone: An empirical investigation - Ozolina C. E Haffner; Alfred J. H. Aruna; Kormay Adams (West African Journal of Monetary and Economic Integration, 2017)
The impact analysis of domestic debt on economic growth in Sierra Leone had over the years, received surprisingly little empirical attention. This study which covers the period 1970 to 2015, therefore, seeks to assess the impact of domestic debt on economic growth in Sierra Leone. Following some schools of thought which opine that the growth of domestic debt beyond a sustainable level adversely affects growth performance, mainly through the crowding out of private sector credit, we seek to investigate at what level does domestic debt exert deleterious effect on economic growth in Sierra Leone. Preliminary investigations reveal that our series are of different orders of cointegration and therefore justify the application of the Autoregressive Distributed Lag (ARDL) model. The regression results of the model show that both in the short and long runs domestic debt exerts negative impact on economic growth. Further, treasury bills rate also negatively affects economic growth, while private sector credit and net investment impact positively on economic growth. The paper also found that above the ratio of 20 percent of domestic debt to GDP, investment and private sector credit are crowded out, reinforcing "debt overhang". In view of these findings, it is recommended that the government of Sierra Leone should reduce the level of domestic borrowing and also improve efficiency by utilising domestic debt for more productive economic activities, such as: promoting development in the financial sector to enhance private sector and investment growth.
Keywords: E62; O4; C51; 330; Domestic Debt; Economic Growth; Autoregressive Distributed Lag (ARDL)